Five lignans from the mangrove Rhizophora stylosa Griff. - Thanh Huong, Phan Thi; Thanh, Nguyen Van; Diep, Chau Ngoc; Cuong, Nguyen The; Cuong, Nguyen Xuan; Nam, Nguyen Hoai; Thai, Tran Huy; Kiem, Phan Van; Minh, Chau Van (Vietnam Journal of Chemistry, 2015)
Five lignans (-)-(7R,8S)-dihydrodehydrodiconiferyl alcohol (1), (7S,8R)-3,3¢,5-trimethoxy-4¢,7-epoxy-8,5¢-neolignan-4,9,9¢-triol (2), (+)-isolariciresinol (3), polystachyol (4), (+)-pinoresinol (5) were isolated from the mangrove plant Rhizophora stylosa Griff.. The chemical structures of these compounds were elucidated by analysis of their NMR spectra and compared with those reported references. All these compounds were isolated from this plant for the first time.